Penerapan Algortima Support Vector Machine (SVM) Untuk Prediksi Tingkat Kelulusan Siswa SMA - Wulandari, Cindi; Bimastari Aviani, Tri Hasanah; Rian Saputra (STMIK Budi Darma, 2024)
Graduation is the desire of every student to be able to complete their studies, and to achieve graduation, students must complete stages such as taking 6 semesters of learning with a school exam score for each subject above 70, and this is a rule in the school. In this study, researchers used student data for the 2022/2023 school year, which researchers took in senior high school number one Lubuklinggau. The method used by the researchers is data mining. Data mining is a term used to describe knowledge discovery in databases. The algorithm the researchers use to predict graduation is the Support Vector Machine (SVM) algorithm because it is able to predict good graduation. In predicting graduation, the accuracy value is 98.81% for XIIth grade students, 96.49% for XIth grade students, and 98.25% for Xth grade students.